Does Business Ethics Disclosure Contribute to ESG Disclosure and ESG Performance on Firm Value? - Triwacananingrum, Wijaya; ., Rahmawati; ., Djuminah; Probohudono, Agung Nur (Journal of Ecohumanism, 2024)
Purpose: This study investigates whether Business Ethics Disclosure (BED) contributes to Environmental, Social, and Governance (ESG) disclosure and ESG performance, and how these factors influence firm value.Methods: Using data from publicly traded companies listed on the Indonesia Stock Exchange (IDX), we employ multiple regression analysis to examine the relationships between BED, ESG disclosure, ESG performance, and firm value.Findings: Our results indicate that BED significantly moderates the relationship between ESG disclosure and firm value. While ESG disclosure alone does not consistently impact firm value, the inclusion of BED enhances the positive effects of ESG practices on firm valuation.Novelty: This study contributes to the literature by highlighting the moderating role of business ethics in the ESG performance-firm value nexus, offering new insights into the interplay between ethical disclosures and ESG outcomes.Research Implications: The findings suggest that companies should integrate ethical disclosures into their ESG strategies to improve firm valuation. Policymakers and regulators are encouraged to establish comprehensive reporting standards that include ethical practices to enhance transparency and investor confidence.